2006
DOI: 10.1007/s00209-005-0871-0
|View full text |Cite
|
Sign up to set email alerts
|

Weak type estimates for maximal operators with a cylindric distance function

Abstract: We establish sharp weak-type estimates for the maximal operators T λ * associated with cylindric Riesz means for functions on H p (R 3 ) when 4/5 < p < 1 and λ = 3/ p − 5/2, and when p = 4/5 and λ > 3/ p − 5/2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This type of restriction on p has been occurred in [1,2]. In [1] it was observed that this restriction is due to the singularities in the interior of the unit disc {ξ : ρ(ξ ) 1}. Actually if P is a square, then the regularity of the multiplier breaks down along line segments connecting the origin and the vertices of the rectangle so the increase of the power δ does not linearly improve the differentiability of the multiplier.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This type of restriction on p has been occurred in [1,2]. In [1] it was observed that this restriction is due to the singularities in the interior of the unit disc {ξ : ρ(ξ ) 1}. Actually if P is a square, then the regularity of the multiplier breaks down along line segments connecting the origin and the vertices of the rectangle so the increase of the power δ does not linearly improve the differentiability of the multiplier.…”
Section: Introductionmentioning
confidence: 90%
“…It is worthy of noticing that there is restriction on p. This distinguishes Marcinkiewicz-Riesz means from Bochner-Riesz means. This type of restriction on p has been occurred in [1,2]. In [1] it was observed that this restriction is due to the singularities in the interior of the unit disc {ξ : ρ(ξ ) 1}.…”
Section: Introductionmentioning
confidence: 93%
“…As for p < 1, it has been obtained for k = 2 that the maximal cylinder operator is of weak type (p, p) on H p (R 3 ) when 4 5 < p < 1 and δ = 3( 1 p − 1) + 1 2 , or when p = 4 5 and δ > 3( 1 p − 1) + 1 2 in [7]. It has been also shown that the above estimates are sharp.…”
Section: Introductionmentioning
confidence: 96%
“…However the existence of a disc in the product causes a more interesting feature of the operator due to the non-vanishing curvature of the boundary of the disc. The results in [7,17] are on the multiplier associated with a product of a disc and one interval and those in [12,13] are on the multipliers associated with a product of only intervals. Even though operators of the first type conveys property caused by the curvature, operators of the second type also have interesting mapping property because of the interactions between intervals.…”
Section: Introductionmentioning
confidence: 99%
“…P. Taylor improved the ranges of p and δ for higher dimensions R n (n 3) in [11]. For the case of p < 1, it is known that the maximal operator associated with the radial cylinder multiplier (1 − max |ξ |, |ξ 3 | ) δ + satisfies sharp weak type (p, p) estimates on H p R 3 when 4/5 < p < 1 and critical index δ = δ(p) := 3(1/p − 1) + 1/2, or p = 4/5 and δ > δ(p) in [3].…”
Section: Introductionmentioning
confidence: 98%